Indocyanine Green Fluorescence to Evaluate Nasoseptal Flap Viability in Endoscopic Endonasal Cranial Base Surgery - Kerr, Edward E.; Jamshidi, Ali; Carrau, Ricardo L.; Campbell, Raewyn G.; Filho, Leo F. Ditzel; Otto, Bradley A.; Prevedello, Daniel M. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives The pedicled nasoseptal flap (NSF) has dramatically reduced postoperative cerebrospinal fluid leakage following endoscopic endonasal approach (EEA) surgery. Although rare, its arterial supply may be damaged during harvest or may be preoperatively damaged for numerous reasons. Early recognition permits harvesting a contralateral flap before sacrificing its pedicle as part of the surgical exposure or use of an alternative flap.Design Technical feasibility study and case series.Setting Tertiary care university-associated medical center.Participants Five patients requiring an EEA with NSF reconstruction.Main Outcome Measures During NSF harvest, intravenous indocyanine green (IVICG) was administered, and a customized endoscopic system was used to visualize the emerging fluorescence. At the end of each case, just before final positioning of the NSF, additional IVICG was administered, and the custom endoscope was again introduced to evaluate fluorescence.Results In four patients, the entire NSF fluoresced brightly with IVICG on initial harvest and before final positioning. One patient showed heterogeneous fluorescence of the pedicle and distal parts of the NSF at both stages. All NSFs healed well without complication.Conclusion IVICG facilitates real-time evaluation NSF's arterial supply. This may provide early recognition of arterial compromise, allowing the harvest of alternate flaps or modification of surgery.
Keywords: indocyanine green; ICG; fluorescence; indocyanine green fluorescence; indocyanine green endoscope; endoscopic endonasal; nasoseptal flap; nasoseptal artery; skull base